2021
DOI: 10.47476/jat.v4i1.2021.149
|View full text |Cite
|
Sign up to set email alerts
|

Gamifying Audio Description Training

Abstract: State-of-the-art training methods for audio description (AD) are essential in preparing future professionals to meet the demand for accessible media content. Gamification, the application of game elements in non-game contexts, has been gaining increasing scholarly attention in the field of teaching and learning over the past few years. It is considered an effective pedagogical approach and has been applied in diverse contexts but not yet in AD training. This paper first provides a brief review of current AD te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Towards the end of their article, the authors reported the students’ perceptions of the internship as part of the intern assessment, and summarised the sub-competencies that the students perceived to have acquired through the internship experience. Zhang (2021) reported on the use of gamification approaches in ADT. After reporting on the activity design and the process of gamification, Zhang gave an account of the students’ perceptions of, and reflections on, this practice.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Towards the end of their article, the authors reported the students’ perceptions of the internship as part of the intern assessment, and summarised the sub-competencies that the students perceived to have acquired through the internship experience. Zhang (2021) reported on the use of gamification approaches in ADT. After reporting on the activity design and the process of gamification, Zhang gave an account of the students’ perceptions of, and reflections on, this practice.…”
Section: Literature Reviewmentioning
confidence: 99%